An oscillation criterion for inhomogeneous Stieltjes integro-differential equations - M. A. El-Sayed (International Journal of Mathematics and Mathematical Sciences)
The aim of the paper is to give an oscillation theorem for inhomogeneous Stieltjes integro-differential equation of the form p(t)x′+∫atx(s)dσ=f(t). The paper generalizes the author's work [2].